2021
DOI: 10.1002/pbc.29115
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of BRAFV600E in patients with cholestasis, sclerosing cholangitis or liver fibrosis secondary to Langerhans cell histiocytosis

Abstract: The abstract of this research has been submitted to the virtual 36th Annual Meeting of the Histiocyte Society (October and November 2020) titled "High prevalence of BRAFV600E in patients with cholestasis, sclerosing cholangitis, or liver fibrosis secondary to Langerhans cell histiocytosis" and was published in the Pediatric Blood & Cancer journal, and the manuscript has been previously submitted to this journal as a Research Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Our study is the first to describe the clinical phenotype of histiocytosis patients with a BRAF Δβ3-αC , and showed a high frequency of sclerosing cholangitis and vulvar manifestations, which are typical LCH manifestations but usually rarely observed. In previous published cohorts of adults, liver manifestations are described in 10-15% of LCH cases 10 , and a study of 14 pediatric patients with LCH and liver involvement showed a 100% prevalence of BRAF V600E mutation 11 .Vulvar manifestations have only been described in some cases series 12 .…”
mentioning
confidence: 99%
“…Our study is the first to describe the clinical phenotype of histiocytosis patients with a BRAF Δβ3-αC , and showed a high frequency of sclerosing cholangitis and vulvar manifestations, which are typical LCH manifestations but usually rarely observed. In previous published cohorts of adults, liver manifestations are described in 10-15% of LCH cases 10 , and a study of 14 pediatric patients with LCH and liver involvement showed a 100% prevalence of BRAF V600E mutation 11 .Vulvar manifestations have only been described in some cases series 12 .…”
mentioning
confidence: 99%